2021
DOI: 10.1007/s12666-021-02418-z
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Nickel–Titanium Thin-Film Shape Memory Alloy Fabricated by Magnetron Sputtering and Influence of Process Parameters

Abstract: This paper discussed the fundamentals of NiTi shape memory alloy and its applications in advanced scientific fields. Currently, the world is focusing on miniaturized systems for various industrial and functional applications. The thin-film shape memory NiTi alloy plays a crucial role in MEMS/NEMS industry in fabrication of microdevices. In this article, the NiTi phase diagram along with the shape memory effect and superelasticity has also been explained. Among several types of fabrication techniques for NiTi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…The heattreatment temperature is critical since, if low, it might not be enough to fully crystallize the films. On the other hand, a temperature higher than necessary can promote the precipitation of undesired phases, such as NiTi 2 , Ni 3 Ti, and oxides, which can influence the films' phase transformation temperatures, as well as the mechanical properties [7,15]. In addition, the mechanical properties are also influenced by grain growth during the heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The heattreatment temperature is critical since, if low, it might not be enough to fully crystallize the films. On the other hand, a temperature higher than necessary can promote the precipitation of undesired phases, such as NiTi 2 , Ni 3 Ti, and oxides, which can influence the films' phase transformation temperatures, as well as the mechanical properties [7,15]. In addition, the mechanical properties are also influenced by grain growth during the heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The effective stimulus is either in the form of heat generated by thermal energy or electrical energy or by the application of loads through which phase transformation occurs to recover the shape. [1][2][3][4][5] The widely used SMA is a nickel (Ni)-titanium (Ti) alloy popularly known as Nitinol. As of today, NiTi SMA is found to be applied in electrical, mechanical, and medical fields in the form of actuators, valves, couplings, sensing devices, lifting devices, auto switch, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works on this topic have been carried out on TiNi SMA [ 17 ], and thin films of this alloy have been produced by a variety of techniques. DC sputtering deposition [ 19 , 20 , 21 , 22 ] and RF magnetron sputtering [ 23 , 24 , 25 ] have been the most used techniques, and were recently reviewed [ 26 , 27 ]. However, other techniques are also used, such as co-evaporation [ 28 ], pulsed laser deposition [ 29 ] and e-beam evaporation [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput combinatorial thin films production [ 31 , 32 ] was developed to optimize the required concentration in ternary and quaternary alloys based on the TiNi system [ 33 , 34 ]. In contrast to the hundreds of publications on TiNi SMA thin films [ 17 , 18 , 26 , 27 ], only a few works have been devoted to producing and characterizing Cu-based SMA thin films [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Nevertheless, recent studies have shown that at the micro- and nanoscales [ 44 , 45 ], Cu-Al-Ni SMA exhibits shape memory and superelastic behavior superior to those of Ti-Ni, with excellent cycling behavior at these small scales [ 46 ].…”
Section: Introductionmentioning
confidence: 99%